Easy Questions, Evil Answers - Poskitt, Kjartan; Illustrated by Reeve, Philip (London Scholastic, 2010)
How can you make a liar tell the truth? How many people in the world share your birthday? Easy Questions, Evil Answers provides the answers to these questions and more. It's the perfect read for anyone who's ever wondered just how many footballs you can fit in a swimming pool and how long it takes to count to a million.
Include Illustrations
Keywords: Mathematics